Health Literacy and Medication Adherence Among Elderly Hypertensive Patients in Indonesian Primary Healthcare: A Cross-Sectional Study - Yunita Nita; Abdul Rahem; Riza Alfian; Irma Susanti (Journal of Public Health and Pharmacy, 2026)
Introduction: Health literacy plays a pivotal role in chronic disease care, including hypertension, by influencing patients’ ability to understand health information and maintain long-term treatment adherence. However, evidence regarding its correlation with medication adherence among elderly populations remains limited, especially in developing countries with diverse socioeconomic and educational backgrounds. Accordingly, this investigation aimed to examine the association between health literacy and adherence to medication among older adults with hypertension residing in East Java, Indonesia. Methods: The study employed a cross-sectional design and was implemented from February to June 2024 at the 2 Primary Healthcare Centers in Lamongan, East Java province, Indonesia. Participants were eligible if they were diagnosed with hypertension, were at least 60 years of age, and had received antihypertensive treatment for no less than three months. The pill count method was used to evaluate medication adherence, with adherence defined as a score >80%. Participants’ health literacy levels were measured using the Indonesian version of the validated HLS-EU-SQ10 instrument., and the results were classified into four categories: inadequate, problematic, sufficient, and excellent. The relationship between variables was evaluated using Spearman’s rank correlation analysis. Results: A total of 212 patients were enrolled, the participants were predominantly female (75%), aged between 60–69 years (80%), and had low education. Most patients were prescribed amlodipine as monotherapy or in combination with other drugs. Health literacy levels were predominantly problematic (42.9%) and inadequate (40.1%). Meanwhile, 78.8% of the patients exhibited good adherence to medication. A weak positive correlation identified between health literacy and medication adherence (r=0.210, p=0.002). Conclusion: These findings suggest a significant weak correlation between health literacy and adherence to medication among elderly with hypertension. Health literacy may therefore be considered an important factor in hypertension management to support optimal therapeutic outcomes in elderly populations.